Cytomegalovirus and Human Herpesvirus 6 and 7: Diseases and Diagnosis in Transplantation - Paul D Griffiths (Canadian Journal of Infectious Diseases)
Similarities and differences in the epidemiology of cytomegalovirus (CMV), human herpesvirus 6 (HHV-6) and human herpesvirus 7 (HHV-7) infections are reviewed. Several distinct laboratory methods have been described for each virus. For CMV in immunocompromised patients, infection is best diagnosed by identifying active infection using routine surveillance cultures. Patients with active infection can then be entered into trials of suppressive therapy (where virus excretion is from the urine or saliva) or pre-emptive therapy (where excretion is detected systemically). For HHV-6 and HHV-7, only anecdotal cases of associations with disease in immunocompromised patients have been reported. Recommendations cannot therefore be made about appropriate diagnostic strategies or about treatment since it is not clear if these viruses are pathogens or passengers.